Continuity of care by cardiothoracic nurse practitioners: Impact on outcome. (October 2014) - Southey, Dawn; Mishra, Pankaj Kumar; Nevill, Alan; Aktuerk, Dincer; Luckraz, Heyman
Objectives: There have been recent reports on increased mortality in British National Health Service hospitals during weekends. This study aimed to assess the impact on patient care following the introduction of nurse practitioner cover for the cardiothoracic ward, including weekends. Methods: Prospectively collected and validated data of patients operated on from January 2005 to October 2011 were analyzed. The patients were grouped according to era: before ( n = 2385) and after ( n  = 3910) the introduction of nurse practitioners in October 2007. Results: There were no significant differences in preoperative patient characteristics such as age, logistic EuroSCORE, sex, smoking, and extracardiac vascular problems. There were more patients from an Asian background ( p  < 0.01), more with noninsulin-dependent diabetes ( p  < 0.01), and more requiring urgent cardiac surgery ( p  < 0.01) in the later era. Following the introduction of nurse practitioner grade, there was a decrease in the rate of cardiac intensive care unit readmission from 2.6% to 1.9% ( p  = 0.05) and length of hospital stay from 10 to 8 days ( p  < 0.01). There was a significant improvement in overall survival after cardiac surgery from 96.5% to 98.0% ( p  < 0.01). Logistic regression analysis confirmed that the presence of nurse practitioners on the ward was the strongest predictor of survival with an odds ratio of 1.9 (95% confidence interval: 1.23–3.01). Conclusion: The introduction of the nurse practitioner grade to provide continuity in patient care including at weekends has been confirmed to improve patient outcomes including survival after cardiac surgery.